Pharmaceutical and Pharmacokinetic Aspects of Nanoformulation Based Drug Delivery Systems for Anti-cancer Drugs - Singh, Arun K.; Bahadur, Shiv; Yadav, Deepika; Dabas, Hunny (Current Pharmaceutical Design, 2023)
Many nanodrug delivery systems used with various routes of administration have been developed recently. These may be dendrimers, nanocrystals, emulsions, liposomes, solid lipid nanoparticles, micelles, or polymeric nanoparticles. The nanodrug delivery systems may improve effectiveness, safety, physicochemical qualities, and pharmacokinetic/pharmacodynamic profile. Functionalized nanodrug delivery systems can increase the half-life, improve the bioavailability of orally administered pharmaceuticals, and target tissue distribution. By decreasing the number of dosage intervals required, increasing the magnitude of the intended pharmacological effects, and decreasing the severity of undesirable systemic side effects, nanodrug systems show promise for improving treatment adherence and clinical results. Nanodrugs have been demonstrated to exhibit cytotoxicity, oxidative stress, inflammation, and genotoxicity in vitro and in vivo; however, this attention has recently been refocused on their potentially harmful potential owing to their beneficial pharmacokinetic features for the treatment of cancer. Researchers require a more profound knowledge of the pharmacokinetic and safety aspects of nanodrugs and the limits of each administration route to continue creating safe and efficacious nanodrugs with high therapeutic potential. The benefits and risks associated with pharmacokinetics have been highlighted in this article, which describes the current state of nanodrug system development.
Keywords: dendrimers